IDENTIFICATION AND MOLECULAR CHARACTERIZATION OFKOCHO SPOILAGE FUNGI COLLECTED FROM DIFFERENT AREA OFGURAGE ZONE, ETHIOPIA (Applied Biological Research, 2024)
Enset is a main food crop in Ethiopia, around 20% of the population depend on it. Understanding the fermentation process is critical for optimum enset utilisation because kocho is one of the most important enset products consumed as a key energy source and serves as a staple and co-staple diet for many people. Fermented kocho is frequently stored in pits lined with enset leaves.During the fermentation process, a piece of the kocho can be withdrawn for consumption or sale at any moment. When kocho is withdrawn from the pit for mixing or usage, it is susceptible to contamination from a variety of microorganisms. The rotting microbes of this vital fermented food are little understood. Thus, the objective of this research was to identify kocho spoilage fungi collected from different area of Gurage Zone of Ethiopia. Ten spoilage kocho samples were gathered in this study from various farm and market sites. The samples were packed in sterile Falcon tubes, placed on ice, and transported to Wolkite University's Biotechnology Molecular Laboratory for morphological and biochemical characterization, as well as DNA isolation and PCR amplification of the internal transcribed spacer region of the gene at MRCET's molecular advanced laboratory in Addis Ababa, Ethiopia. PCR results were sequenced and each fungal isolate was identified using an automated DNA sequencer from MRC-Holland in Amsterdam. 22 fungus species were identified using morphological tests, biochemical tests, and molecular analysis. Sequence analysis revealed that four of the 22 fungal isolates were identified as different Alternaria strains, three as different penicillium strains, two as goitreucum, one as galactomyce, two as schizophyllum, two as aspergillus, and one as agaricaceae spp. Further research on the detected fungi should be carried out to determine the most damaging and deteriorating strain in order to properly control and manage kocho spoilage fungi.
Keywords: DNAsequencing; ITSDNAregiongene; kochospoilage organisms